SYNTHESES AND ANTIOXIDANT ACTIVITIES OF SOME HYDROXY DIMETHOXY CHALCONE DERIVATIVES - VH, Elfi Susanti (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2014)
Four (4) hydroxy dimethoxy chalcones derivatives were synthesized by Claisen-Schmidt condensation of hydroxyacetophenone with 3,4-dimethoxybenzaldehyde using conventional method and grinding technique. The synthesized compounds were characterized by spectroscopy (IR, 1H-NMR and 13C-NMR). Synthesis of the hydroxy dimethoxy chalcone using grinding method is better than the conventional method. The synthesis using grinding method require a low concentration base, shorter reaction (15min) and higher yield (70-84%). Â The antioxidant activity of the compounds was determined by DPPH method, showed that Â 2,5-dihydroxy-3,4-dimethoxy chalcone have the highest antioxidant activity.Key word: hydroxy dimethoxy chalcone, Claisen-Schmidt condensation, grinding, DPPH method